Slack Resources, Audit Committee, Board Feminism on the Quality of Corporate Social Responsibility Disclosure of Mining Industry Companies - Rumkabu, Faradila Mince; Mutmainnah, Mutmainnah; Pasolo, Muhammad Ridhwansyah (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to examine whether slack resources, audit committee effectiveness, and board feminism influence the quality of corporate social responsibility (CSR) disclosure. Research Design and Methodology: This study employs a quantitative research method. The population consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample was selected using a purposive sampling technique. The study utilizes panel data as its data source, and data collection was conducted using the documentation method. Findings and Discussion: The analysis results indicate that slack resources and audit committees do not significantly affect the quality of CSR disclosure. However, board feminism does have a significant influence on this quality, suggesting that gender diversity on corporate boards enhances the transparency and comprehensiveness of CSR reporting. Implications: This study provides insights and a deeper understanding of the role of audit committees and gender diversity on the quality of CSR disclosure. It can serve as a valuable reference for future research and offer considerations for companies and policymakers in enhancing CSR practices through improved governance structures and board diversity.